Characterization of the DNA helicase PDH45 from Pisum sativum L. - Hoi, Pham Xuan; Quy, Tran Duy; Nghia, Phan Tuan; Tuteja, Narendra (Academia Journal of Biology, 2015)
The transient opening of the duplex DNA is a prerequisite step in many processes of the DNA metabolism. DNA helicases catalyze the unwinding of the double stranded DNA and in some cases, the double stranded RNA and DNA-RNA hybrids to create single stranded templates by disrupting the hydrogen bonds between two strands and thus play an important role in DNA replication, repair, recombination, transcription and translation. The pdh45, the first plant DNA helicase gene which has been cloned, is over-expressed and partially characterized (Pham et al., 2000). Here, the gene pdh45 is found to be an intronless and single copy gene. The gene is expressed almost at the same level at different stages of flower development, except for the F1 stage and its expression is stimulated by the blue light. Enzyme PDH45 can bind to poly(A)RNA. The unwinding activity of the enzyme PDH45 is salt- and Mg2+-dependent. The enzyme PDH45 is heat labile and its activity is destroyed by the incubation with the trypsin. The helicase activity of the enzyme PDH45 is totally inhibited by 5 mM EDTA, 45 mM ammonium sulfate, 100 mM potassium phosphate (pH 8,0) or M13 ssDNA (30 mM). However, M13RFI DNA, E. coli t-RNA, pea total RNA and Poly[A], Poly[C], Poly[G] and Poly[U] at 30 mM have no effect on the DNA unwinding activity of the enzyme PDH45. The enzyme shows no activity when ATP in the reaction mixture is replaced by ATPgS or ADP or AMP and when Mg2+ is replaced by other divalent cations such as Zn2+, Cu2+, Ni2+, Ag2+ and Co2+. However, Mn2+ and Ca2+ (at 0,6 mM concentration) support 89% and 14% of the activity, respectively. The overall divalent cation requirement is Mg2+>Mn2+>>Ca2+. At a concentration of 200 mM KCl or NaCl, the unwinding activity is not significantly inhibited. The MgCl2 can be replaced by MgSO4 or Mg (CH3COO)2 without any effect on its activity. These results suggest that the enzyme PDH45 could be an important multifunctional protein involved in the protein synthesis and maintaining the basic activities of the cell.